2013
DOI: 10.1364/ol.38.003355
|View full text |Cite
|
Sign up to set email alerts
|

Photonic microwave amplification for radio-over-fiber links using period-one nonlinear dynamics of semiconductor lasers

Abstract: For radio-over-fiber links, microwave-modulated optical carriers with high optical modulation depth are preferred because high optical modulation depth allows generation of high microwave power after photodetection, leading to high detection sensitivity, long transmission distance, and large link gain. This study investigates the period-one nonlinear dynamics of semiconductor lasers for optical modulation depth improvement to achieve photonic microwave amplification through modulation sideband enhancement. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In the same panel, we see the emergence of the socalled sideband locking regions corresponding to a detuning Δ=±ω m , in which the slave laser is locked on the modulation sideband of the modulated injection signal. The emergence of clear P1 dynamics in this range is therefore perfectly in line with previous studies as this regime has been identified as a promising solution for high-frequency signal generation [33][34][35][36]. Going one step further to ω m =5 in panel (a.5), we remark that the features of the extrema map obtained when no modulation of the injection signal is present are resurfacing, especially for lower values of the injection rate.…”
Section: Evolution Of the Detuning-injection Rate Map For Stronger/fasupporting
confidence: 90%
See 1 more Smart Citation
“…In the same panel, we see the emergence of the socalled sideband locking regions corresponding to a detuning Δ=±ω m , in which the slave laser is locked on the modulation sideband of the modulated injection signal. The emergence of clear P1 dynamics in this range is therefore perfectly in line with previous studies as this regime has been identified as a promising solution for high-frequency signal generation [33][34][35][36]. Going one step further to ω m =5 in panel (a.5), we remark that the features of the extrema map obtained when no modulation of the injection signal is present are resurfacing, especially for lower values of the injection rate.…”
Section: Evolution Of the Detuning-injection Rate Map For Stronger/fasupporting
confidence: 90%
“…Alternatively, the slave laser can also be locked on the sidebands induced by the modulation of the optical injection, which forces the laser to generate so-called period-1 (or P1) oscillations [32]. This technique has been shown to be an excellent means to amplify [33], convert [34] or generate various high-frequency signals [35,36]. Nevertheless, the behaviour of a semiconductor laser subject to optical injection with a simple harmonic modulation has, to the best of our knowledge, not been thoroughly investigated so far, even if very recent works showed that this problem also caught the interest of other groups [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Self-adaptation to changes in the operating microwave frequency is feasible, and stable operation under fluctuations of the injection level and frequency is achievable. Furthermore, the P1 dynamics have also been studied for photonic microwave amplification [12] by applying the red-shifted cavity resonance enhancement. The amplification can be achieved for a broad microwave range, up to at least 60 GHz, and for a wide gain range, up to at least 30 dB.…”
Section: Introductionmentioning
confidence: 99%
“…The P1 oscillation inherently contains phase noise that can be suppressed by methods such as optical feedback, optoelectronic feedback, and low-sensitivity operation [4,5,25,26]. The P1 oscillation hence has been demonstrated for a number of applications, including radio-over-fiber communication [27], amplitude-to-frequency modulation format conversion [28], frequency multiplication [21,29], and photonic microwave amplification [30]. However, the generation of FMCW signals has yet to be explored using the P1 oscillation through incorporating modulation on its microwave frequency.…”
mentioning
confidence: 99%